THE ROLE OF DIGITAL LITERACY IN OPTIMIZING STUDENTS' PERSONAL BRANDING THROUGH SOCIAL MEDIA AT SMK MASTER INDONESIA - Murdiyono Murdiyono; Didi Sukardi; Rahmatullah Rahmatullah; I Nyoman Suri Adnyana (Yayasan Nusantara Hasana Berdikari, 2024)
The development of information technology and social media provides significant opportunities for students to build positive personal branding in the digital space. This study aims to analyze the role of digital literacy in optimizing students' personal branding through social media at SMK Master Indonesia. The research method used was a quantitative approach, distributing questionnaires to students as research respondents. The results show that a good level of digital literacy can improve students' ability to use social media creatively, ethically, and productively, thereby building a positive self-image in the educational environment and society.